If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 40(x + 2) Reorder the terms: 7 = 40(2 + x) 7 = (2 * 40 + x * 40) 7 = (80 + 40x) Solving 7 = 80 + 40x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40x' to each side of the equation. 7 + -40x = 80 + 40x + -40x Combine like terms: 40x + -40x = 0 7 + -40x = 80 + 0 7 + -40x = 80 Add '-7' to each side of the equation. 7 + -7 + -40x = 80 + -7 Combine like terms: 7 + -7 = 0 0 + -40x = 80 + -7 -40x = 80 + -7 Combine like terms: 80 + -7 = 73 -40x = 73 Divide each side by '-40'. x = -1.825 Simplifying x = -1.825
| -4-5=3-6a | | 3x^4(5x^2-4x-5)=0 | | 6x-3y=-6 | | 3(-3x+8)=-7(4x+2) | | 6t+30=-36 | | 8-x^2=2x | | -5-12=3 | | -2x-7=-5 | | 6x^2+20=29x | | (x-3)(x-4)=30 | | 6(2y-8)+3=15 | | 16+5*(x-6)=20 | | 8+4n=-4 | | 7x-5=-12 | | -2(-2x-10)=2(-2-4) | | -3x-15=3 | | 38x=6x^2+12 | | 4x+3y=31 | | 10x+x+7=29 | | 5(k+2)=3(k+8) | | (2x+5)=(5x-25) | | 0.75e-8=0.25(5p+8)-0.5p | | 5x+9.2=19.7 | | 4b^3-24b^2=108b | | -6x+16=-8 | | x^3+12x^2+54x+11=6 | | 0.5(6m-10)=3m-5 | | Y=-x+8 | | 7X+8X-7X+10=22 | | c^2+6c=27 | | x^3+12x^2+54x+5=0 | | -16x+92=12 |